THE IMPLEMENTATION OF HERRINGBONE TECHNIQUE IN WRITING CLASS OF JUNIOR HIGH SCHOOL STUDENT - Ayu Dewanti, Novita (Widya Wacana: Jurnal Ilmiah, 2017)
AbstractWriting is not only the act of arranging graphic symbols, but writing is also an integral part of communication when the other person is not there in front of us. It means that written language includes the organization of words, phrases, clauses, and sentences into coherent and cohesive paragraphs and texts. The aims of the study are as following : (1) To find out whether the use of Herringbone technique in teaching English improves the students’ writing skill at SMP Negeri 7 Surakarta in 2017/2018 academic year. (2) To describe the implementation of Herringbone technique to improve the students’ writing skill of the eighth grade students at SMP Negeri 7 Surakarta in 2017/2018 Academic Year.This action research was carried out at the eighth grade students of class VIII H in SMP Negeri 7 Surakarta consisted of 31 students, 16 female and 15 male. The researcher conducted 2 cycles of classroom action research. In collecting the data, interview, observation, documentation and test were used. In analyzing the data, the researcher used Qualitative and Quantitative data analysis.The result of this research showed that herringbone technique improved the students writing skill. The improvements of the students writing skill were seen from the results of the tests. The students mean score in pre-test was (46,45) . The students mean score in post-test 1 was (68,29)  and the students score in post-test 2 was (78,42), there was a significant result between pre-test and post-test 2. The technique also made the students felt fun and interested. Keywords : Writing Skill, Herringbone technique, Classroom Action Research. AbstrakMenulis bukan hanya tindakan mengatur simbol grafis, tetapi menulis juga merupakan bagian integral dari komunikasi ketika orang lain tidak ada di depan kita. Ini berarti bahwa bahasa tertulis mencakup pengorganisasian kata, frasa, klausa, dan kalimat ke dalam paragraf dan teks yang koheren dan kohesif. Tujuan dari penelitian ini adalah sebagai berikut: (1) Untuk mengetahui apakah penggunaan teknik Herringbone dalam mengajar Bahasa Inggris meningkatkan keterampilan menulis siswa di SMP Negeri 7 Surakarta pada tahun akademik 2017/2018. (2) Untuk mendeskripsikan penerapan teknik Herringbone untuk meningkatkan keterampilan menulis siswa siswa kelas VIII di SMP Negeri 7 Surakarta pada tahun akademik 2017/2018. Penelitian tindakan ini dilakukan pada siswa kelas VIII kelas VIII H di Indonesia. SMP Negeri 7 Surakarta terdiri dari 31 siswa, 16 perempuan dan 15 laki-laki. Peneliti melakukan 2 siklus penelitian tindakan kelas. Dalam mengumpulkan data, wawancara, observasi, dokumentasi dan tes digunakan. Dalam menganalisis data, peneliti menggunakan analisis data Kualitatif dan Kuantitatif. Hasil penelitian ini menunjukkan bahwa teknik herringbone meningkatkan keterampilan menulis siswa. Peningkatan keterampilan menulis siswa terlihat dari hasil tes. Nilai rata-rata siswa dalam pre-test adalah (46,45). Nilai rata-rata siswa pada post-test 1 adalah (68,29) dan skor siswa pada post-test 2 adalah (78,42), ada hasil yang signifikan antara pre-test dan post-test 2. Teknik ini juga membuat para siswa merasa senang dan tertarik. Kata kunci: Keterampilan Menulis, Teknik Herringbone, Penelitian Tindakan Kelas.